O samba sacramentado: a música na cadência do samba do Quintal do Divina Luz - Gelson Luiz da Silva (2012)
Herein we analyze a roda de samba in several aspects. We try to understand how the sambistas articulate a network of social and musical relations. Our aim has been to verify how the music is performed and how the members of the audience behave when they interact among themselves and with the performers. Initially, we describe the environment and the agents directly involved in the roda de samba: the owner and his or her contractors. Available historiographic data on this theme has allowed us to understand the origin of percussion performances in Brazilian music in different scenarios. These additional references to this kind of music have been extremely important to understand the structure of the environment in which the roda de samba takes place. We have made video-clips and interviews to register the behavior of agents in that network of relations. Through these videos, we have recognized recurrent standards of rhythm that identify the musical style of the group. We have selected the lyrics of outstanding songs composed by some members of the group in order to understand the themes they develop. Readings in philosophy and semiology have allowed us to understand attitudes and positions of the members of the audience of Quintal the place where the research has taken place - as well as the attitude of the musicians. Drawing on the concepts of street, - a public place - as the unknown, the unpredictable, and the concept ofhome, - a private place - as a protected environment, taken from one of the authors used as a reference in this dissertation. We have concluded that the musicians have immersed themselves in a symbiotic process. This process fuses elements of street and home. To sum up, we have perceived some of the conceptions which are presents in the typicallyBrazilian musical phenomenon - Roda de samba.